Generalized Chronic Periodontitis in Elderly Heavy Smokers - Tahnia, Nita Tahnia; Pranoto, Amelia Elizabeth (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Periodontitis is one of the most common periodontal diseases affecting both elderly individuals and heavy smokers. This case report aims to describe the management of a geriatric patient with generalized chronic periodontitis and a history of heavy smoking. A 63-year-old male patient presented with a chief complaint of mobile teeth that had persisted for the past three months. Intraoral examination revealed necrosis, cervical caries, gingival recession, and poor oral hygiene. The treatment included extraction of the mobile teeth and socket curettage to remove necrotic tissue. The patient was prescribed antibiotics and analgesics, followed by a one-week post-operative evaluation. The patient reported no pain or swelling after extraction, and the healing process was satisfactory, with no signs of infection. The patient was also informed about a long-term treatment plan involving the fabrication of a prosthesis. Tooth extraction in patients with chronic periodontitis requires careful consideration of both clinical and non-clinical factors. This case highlights the importance of a comprehensive approach in the management of periodontitis in elderly heavy smokers.